Analisis Faktor yang Berpengaruh dengan Kualitas Pelayanan Rawat Inap RSKDIA Siti Fatimah Kota Makassar - Mulkisnah Mulkisnah; Andi Yusuf; Diana Mirja (Poltekkes Kemenkes Padang, 2024)
The quality of health services, whether good or bad, will affect the level of patient satisfaction because patients will provide responses and assessments of the quality of health services. At RSKDIA Siti Fatimah, there was a decrease in the number of inpatients from 2021 to 2023. The purpose of this study was to determine the factors that influence the quality of inpatient services at RSKDIA Siti Fatimah, Makassar City. The type of quantitative research with a cross-sectional approach, a population of 245 patients and sampling using a simple random sampling technique so that the sample obtained was 71 patients. Data Collection Technique Through Direct Observation Using Questionnaires. Data analysis using Chi Square analysis. The variables studied were: Service Quality, Reliability, Direct Evidence, Responsiveness, Assurance, Empathy. The results of the study found the p value of Reliability with Service Quality (p = 0.012), responsiveness with Service Quality (p = 0.007), assurance with Service Quality (p = 0.002), empathy with Service Quality (p = 0.000), Direct Evidence with Service Quality (p = 0.033), based on the multivariate test, the most influential empathy variable was obtained. Conclusion There is an influence of Reliability, responsiveness, assurance, empathy and Direct Evidence on Service Quality. It is recommended that hospitals maintain good service quality to patients.